2018
DOI: 10.17576/jsm-2018-4708-19
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Asians to Calcium and Vitamin D Rich Foods and Supplements: A Systematic Review

Abstract: The prevalence of osteoporosis is increasing in Asian countries. Optimum calcium intake and vitamin D level are important to prevent osteoporosis. The attitude of the society towards calcium food sources and supplements, as well as sun exposure, influence their bone health practices. This review aimed to summarize the current literature on the attitude of Asians on calcium and vitamin D rich foods and supplements to understand the barriers among the Asians in achieving adequate calcium intake and vitamin D lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A 2018 literature study with 1139 subjects in Singapore, Malaysia, and India, found a prevalence of vitamin D deficiency of 47.8% 24 . Similar to this study, the mean serum 25(OH)D level in the treatment group was 18.2 ± 8.5 ng/mL with 70% (n=19), while the mean in the control group was 14.1 ± 6.3 ng /mL with 88.9% (n=24) so that the majority of research subjects experienced deficiency in the serum level category of 0 -20 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…A 2018 literature study with 1139 subjects in Singapore, Malaysia, and India, found a prevalence of vitamin D deficiency of 47.8% 24 . Similar to this study, the mean serum 25(OH)D level in the treatment group was 18.2 ± 8.5 ng/mL with 70% (n=19), while the mean in the control group was 14.1 ± 6.3 ng /mL with 88.9% (n=24) so that the majority of research subjects experienced deficiency in the serum level category of 0 -20 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the insignificant difference of calcium intake between HPT and non-HPT groups, the overall intake of all participants was lower than the RNI level. It may be due to Asian cultural dietary habits, which commonly involve non-dairy diets 69 , 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The result is comparable with the findings from Hamid et al (2019), where only 2.6% of antenatal mothers in suburban MCH clinics in Selangor, Malaysia achieved the RNI for calcium. It was reported that most Asians were not aware of the importance of calcium for their health and thus, authors suggested that their negative attitude must be corrected (Chan et al, 2018). Both vitamin D and calcium complement each other and are important in maintaining healthy bones and teeth, which is crucial for healthy periodontium during pregnancy.…”
Section: S-ohip(m) Domain and Itemmentioning
confidence: 99%